Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Yan, Xiaobo; Pan, Simiao; Li, Zhihao; Dong, Xiaohui; Tan, Beiping; Long, Shuisheng; Li, Tao; Suo, Xiangxiang; Yang, Yuanzhi (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with Lactobacillus pentosus at 1.0×107, 1.0×108, 1.0×109 CFU/g, respectively. Five kinds of diets were fed to grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results show that: consumption of OFO diet significantly increased muscle crude lipid, total cholesterol and total monounsaturated fatty acids contents, and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper (P < 0.05); wheras the addition of Lactobacillus pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels and increased muscle crude protein content and enhanced muscle hardness, gumminess, chewiness compared with FFO or OFO group (P < 0.05). In addition, ingestion of OFO diet increased significantly muscle phenylalanine content and significantly decreased aspartic acid content (P < 0.05), while the addition of Lactobacillus pentosus restored aspartic acid to the level not significantly different from that of FFO group (P > 0.05), the addition of Lactobacillus pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine and alanine content compared to FFO group at the same time (P < 0.05). Furthermore, the intake of OFO diet would lead to deterioration in muscle flavour quality and increase in noxious odours in grouper, and the addition of Lactobacillus pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly down-regulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system (P < 0.05), which was protected against by the potent antioxidant properties of Lactobacillus pentosus. We recommend the supplementation level of Lactobacillus pentosus to be 1.0×109 CFU/g under the highly oxidised conditions of the present trial fish oil.